The relationship between deontic representations of adolescents and the characteristics of their self-attitude - N.V. Lukyanchenko; L.S. Zakharova; M.I. Alikin (Социальная психология и общество)
Context and relevance. The human world is characterized by a special aspect of assessing obligation, acceptability, desirability. The deontic nature of the social situation of personality development is complicated by the diversity of its contexts and the ambiguity of normative regulations in modern society. Adolescence is a key age for integrating the understanding of social contexts, developing one's own system for determining deontically significant actions and their assessment. The formation of ideas about the surrounding world and evaluative relationships in it is closely connected with the processes of self-awareness, especially in its self-relationship aspect. Objective. To identify the relationship between one's own deontic assessments and the assessments provided by subjects of the near and far circle and the features of their connection with the characteristics of self-attitude in adolescents. Hypothesis. The assumptions were considered that: 1) adolescents' deontic assessments are close to the assessments they attribute to their peers, 2) their own deontic assessments and the assessments they represent of other social subjects are related to varying degrees to the characteristics of self-attitude. Methods and materials. A questionnaire that asks to give a deontic assessment of actions that are significant for adolescents and characteristics of behavior in the variants of their own opinion and the presented opinions of subjects of the near (friends and parents) and distant (peers and adults) circle; "Self-Attitude Test Questionnaire" by V.V. Stolin, S.R. Panteleev; "The Self-Concept Scale for Children" (the "Piers-Harris Children's Self-Concept Scale" method by E. Pierce and D. Harris, adapted by A.M. Prikhozhan). Mathematical processing: comparison of means in standard deviation units, correlation analysis. Respondents of the study: a sample of urban adolescents studying in secondary comprehensive schools, equal in gender composition, a total of 116 people. Results. Adolescents place their own assessments in the intervals between the assessments of their parents, which they consider to be the most prosocial, and the assessments of their peers, which constitute their alternative. Only their own assessments of behavioral manifestations that distinguish the subject from the social context are comparatively high. In the general trend with indicators of positive self-attitude, direct connections have assessments of prosocial actions, and inverse connections have actions of an anti- and asocial orientation. The exception is the positive connections of assessments of criminogenic actions and use of harmful substances attributed to parents, adults, and peers. The most saturated system of direct connections with indicators of positive self-attitude have assessments of manifestations of honesty. Conclusions. The results of the study confirmed the validity of the second hypothesis and did not confirm the first of the proposed assumptions. The teenagers' own assessments are close to the presented assessments of their peers only in relation to egocentric behavior. The data obtained can be used in developing means of psychological support for educational work with teenagers.